PANDAS syndrome – pathophysiology, diagnostic challenges, and treatment approaches - Stopa, Małgorzata; Lewicka, Wiktoria; Semianiuk, Alina (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Pediatric autoimmune neuropsychiatric disorder associated with streptococcal infection (PANDAS) represents a subset of pediatric acute-onset neuropsychiatric syndrome characterized by abrupt obsessive-compulsive and tic symptoms triggered by group A β-hemolytic streptococcus. Despite established diagnostic criteria, PANDAS remains controversial due to limited pathophysiological evidence and the absence of validated biomarkers. The most widely accepted hypothesis suggests molecular mimicry, with anti-neuronal autoantibodies causing immune-mediated damage to the basal ganglia. Diagnosis is essentially clinical, requiring exclusion of other infectious, inflammatory, or metabolic conditions. Treatment strategies are multidisciplinary and include antimicrobial therapy, psychiatric and behavioral interventions, and, in severe cases, immunomodulatory approaches such as corticosteroids, intravenous immunoglobulin, or plasma exchange. Given the relevance of this topic to the pediatric population, further research is required to clarify mechanisms, standardize diagnostic tools, and establish evidence-based treatment guidelines to optimize outcomes for affected children and their families.